Islamic da'wah through a creative ideological approach - U Tun Aung, Maulana Akbar Shah (Journal of Education and Social Science (JESOC), 2016)
Traditional Da’wah activity has been very successful throughout the centuries, as the Muslim population has increased to 2.9 billion today.1 However, it is indeed important to work rigorously for preparation of true and dedicated Muslims among them because many of our Ummah is found to be namely Muslims and the true colour and quality of Muslim has been far away from the reality. The consequences of this unwanted situation causes conversion of Muslims to other religion, production of unqualified followers and leaders, rapid emergence of atheist, secularist, liberalists, extremist, and terrorists in many Muslim nations, continued internal dispute, and civil war in Muslim countries. The reason of befalling fitna and problems on the Ummmah according to my research is not because of the sabotage of western civilization or non-Muslim, it is only for nonappliance of promise by Muslims to their creator and it is the penalty ordered by Allah, SWT. Allah said: And whoever turns away from my remembrance - indeed, he will have a depressed life. (Sura, At Taha, 20:124). Anguish, despair and destruction of Ummah is all around in many Islamic countries and communities. This situation critically highlighted the importance of reminding Muslims to be true Muslims once again, as our Prophet established the best Ummah with his best method of Dawah. Since we have entered in 21th century, the method of Da’wah should also be a kind of creative.